Pertanggungjawaban Pidana Pada Anak Terhadap Pelanggaran Lalu Lintas yang Menyebabkan Kematian - I Made Dwi Satya Anggara; A.A Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum, Universitas Warmadewa, 2020)
Lately, the number of children who often do criminal traffic violations, It is so menghawatirkan because it is not uncommon to traffic violations cause a crash to arise the victim died. Not only that, problems also arises in terms of responsibilities, in this case the victim died from a traffic offence committed. The purpose of this research is to analyse the responsibility of children against traffic offences which cause the victim's death. The method used in writing this essay is primary legal material. Based on the research conducted found that the age of the child greatly influences the overthrow of punishment on the child. Children aged under 14 years can only be charged penalties act whereas the provision of criminal sanctions is a child aged over 14 years to 18 years old according age limit child according to Act No. 35-year 2014 About child protection article 1 point 1. Provision of criminal sanctions of prison-related responsibilities against the crime that he had arranged with the penalty provisions based on Â½ (one-) maximum threat from adults in accordance to article 81 paragraph (2) of Act No. 11 years 2012 about the criminal justice system.